2015
DOI: 10.1002/ldr.2374
|View full text |Cite
|
Sign up to set email alerts
|

Does Biochar Improve Establishment of Tree Seedlings in Saline Sodic Soils?

Abstract: ABSTRACTviminalis and increased the concentration of P, K and S in leaves of A. mearnsii when grown in the low saline sodic soil. The results confirm that there is potential for biochar to assist in reforestation of saline sodic soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 53 publications
6
60
0
1
Order By: Relevance
“…Furthermore, BC is also thought to have potential in improving reforestation in saline-sodic soil possibly through minimisation of salt toxicity in such soils (Drake et al, 2016). This means that BC has a potential for the reclamation of saline-sodic soils.…”
Section: Soil Phmentioning
confidence: 99%
“…Furthermore, BC is also thought to have potential in improving reforestation in saline-sodic soil possibly through minimisation of salt toxicity in such soils (Drake et al, 2016). This means that BC has a potential for the reclamation of saline-sodic soils.…”
Section: Soil Phmentioning
confidence: 99%
“…production. There were increasing evidences suggested that biochar application could help combat salinity stress to plant and improve productivity in saline croplands (Drake et al, 2015;Lashari et al, 2015;Hammer et al, 2014). Akhtar et al (2015) have reported that incorporation of biochar into salt-affected soil could alleviate salinity stress mainly because of its high salt adsorption potential, decreasing osmotic stress by enhancing soil moisture content, and releasing mineral nutrients.…”
Section: −1mentioning
confidence: 99%
“…Although biochar application has shown some variable results, depending on soil type, biochar feedstock, biochar pyrolysis temperature, and other environmental factors; there are a number of potential positive aspects associated with the use of biochar as a soil amendment, including increased soil nutrient availability and uptake by plants (Sigua, Novak, Watts, Johnson, & Spokas, ; Zornoza, Moreno‐Barriga, Acosta, Muñoz, & Faz, ); enhanced organic and inorganic fertilizers use efficiency (Schulz & Glaser, ); increased soil mineral N (NH 4 and NO 3 ) retention (Clough, Condron, Kammann, & Müller, ); reduced nutrient losses and fertilizer demand (Ding et al, ); improved soil physical properties (soil water holding capacity, soil aeration, bulk density, porosity, aggregate stability, infiltration rate, and hydraulic conductivity; Atkinson, Fitzgerald, & Hipps, ; Mukherjee & Lal, ); increased base saturation and liming effect on acidic soils (Wang et al, ); stabilization of heavy metals and reduced bioavailability to plants growing in contaminated soils (Ahmad et al, ; Paz‐Ferreiro, Plasencia, Gascó, & Méndez, ); stimulation of microbial populations and functioning (Zhu, Chen, Zhu, & Xing, ); increased crop performance and productivity (Jeffery, Verheijen, van der Velde, & Bastos, ); enhanced symbiotic N fixation in legumes (Mia et al, ); reduced salinity, drought, and heat stresses impact on plant growth and soil properties (Ali et al, ; Drake, Cavagnaro, Cunningham, Jackson, & Patti, ; Fahad et al, ). In conjunction with chemical fertilizers, biochar improves the nutrient use efficiency of plants by enhancing soil nutrient retention for a longer period of time, and via the slow release of nutrients according to plant requirements (DeLuca, MacKenzie, & Gundale, ).…”
Section: Introductionmentioning
confidence: 99%
“…soil mineral N (NH 4 and NO 3 ) retention (Clough, Condron, Kammann, & Müller, 2013); reduced nutrient losses and fertilizer demand ; improved soil physical properties (soil water holding capacity, soil aeration, bulk density, porosity, aggregate stability, infiltration rate, and hydraulic conductivity; Atkinson, Fitzgerald, & Hipps, 2010;Mukherjee & Lal, 2013); increased base saturation and liming effect on acidic soils ; stabilization of heavy metals and reduced bioavailability to plants growing in contaminated soils Paz-Ferreiro, Plasencia, Gascó, & Méndez, 2017); stimulation of microbial populations and functioning (Zhu, Chen, Zhu, & Xing, 2017); increased crop performance and productivity (Jeffery, Verheijen, van der Velde, & Bastos, 2011); enhanced symbiotic N fixation in legumes (Mia et al, 2014); reduced salinity, drought, and heat stresses impact on plant growth and soil properties Drake, Cavagnaro, Cunningham, Jackson, & Patti, 2016;Fahad et al, 2016). In conjunction with chemical fertilizers, biochar improves the nutrient use efficiency of plants by enhancing soil nutrient retention for a longer period of time, and via the slow release of nutrients according to plant requirements (DeLuca, MacKenzie, & Gundale, 2009).…”
mentioning
confidence: 99%